Neurobehavioral burden of multiple sclerosis with nanotheranostics - Sriramoju B; Kanwar RK; Kanwar JR (Neuropsychiatric Disease and Treatment, 2015)
Bhasker Sriramoju, Rupinder K Kanwar, Jagat R Kanwar Nanomedicine-Laboratory of Immunology and Molecular Biomedical Research (NLIMBR), School of Medicine, Molecular and Medical Research, Faculty of Health, Deakin University, VIC, Australia Abstract: Multiple sclerosis (MS) is a chronic demyelinating neurological disorder affecting people worldwide; women are affected more than men. MS results in serious neurological deficits along with behavioral compromise, the mechanisms of which still remain unclear. Behavioral disturbances such as depression, anxiety, cognitive impairment, psychosis, euphoria, sleep disturbances, and fatigue affect the quality of life in MS patients. Among these, depression and psychosis are more common than any other neurological disorders. In addition, depression is associated with other comorbidities. Although anxiety is often misdiagnosed in MS patients, it can induce suicidal ideation if it coexists with depression. An interrelation between sleep abnormalities and fatigue is also reported among MS patients. In addition, therapeutics for MS is always a challenge because of the presence of the blood–brain barrier, adding to the lack of detailed understanding of the disease pathology. In this review, we tried to summarize various behavioral pathologies and their association with MS, followed by its conventional treatment and nanotheranostics. Keywords: demyelination, behavioral disorders, behavioral tests